Hubungan kepatuhan menjalani terapi hemodialisis dengan kualitas hidup pasien gagal ginjal kronik di RSUD Provinsi NTB: Hubungan kepatuhan menjalani terapi hemodialisis dengan kualitas hidup pasien gagal ginjal kronik di RSUD Provinsi NTB - Sintha Puspitasari; Baiq Leny Nopitasari; Adea Rana Honsa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UNIVERSITAS JENDERAL ACHMAD YANI YOGYAKARTA, 2025)
Chronic Kidney Disease (CKD) represents a global health challenge characterized by progressive and irreversible decline in kidney function, affecting bodily homeostasis and patients' quality of life. Epidemiological data shows a significant increase in prevalence, with four out of every thousand Indonesian residents suffering from CKD. This study aims to analyze the relationship between adherence to hemodialysis therapy and quality of life among chronic kidney disease patients at NTB Provincial Hospital. Using a quantitative research design with a cross-sectional approach, the study was conducted on 70 respondents selected through purposive sampling technique. Data collection utilized the ESRD-AQ questionnaire to measure adherence and KDQOL-SF to assess quality of life, with data analysis using the Gamma correlation test. Results showed the majority of respondents were male (55.7%) with an average age of 46-55 years (34.3%). Patient adherence levels were predominantly high (51.4%) and moderate (45.7%), with the highest adherence domain in hemodialysis attendance (300±0) and lowest in dietary behavior (154.28±65.79). The majority of patients' quality of life was in the good category (50%) with an average score of 68.18. Statistical analysis revealed no significant relationship between hemodialysis adherence and quality of life (p=0.718, r=0.071). This study concludes that the quality of life of hemodialysis patients is influenced by complex factors beyond therapy adherence. It is recommended for healthcare institutions to develop comprehensive educational programs involving psychosocial aspects and family support, as well as improved monitoring in adherence domains that remain low.